Evaluation of the impact of bone-in versus boneless cuts on beef palatability - Farmer, Kaylee Jo (Kansas State University, 2022)
The objective of this study was to determine the palatability traits of beef cuts of differing bone state and quality grade. Paired (n = 12) beef short loins, export ribs, and boneless ribeye rolls of USDA 2/3 Choice and Select were collected from a commercial abattoir. Short loins were fabricated into boneless strip loins with corresponding bone-in tenderloins or bone-in strip loins with boneless tenderloins at Kansas State University (KSU). No further fabrication was necessary for ribeye rolls, thus they remained in native packaging from the processing facility. Product was aged for 28 days and fabricated into 2.5-cm thick steaks. A total of 18 trained sensory panels were conducted. Steaks were cooked on clamshell style grills to a peak temperature of 71°C. Trained panelists were asked to rate samples for initial juiciness, sustained juiciness, myofibrillar tenderness, overall tenderness, beef flavor intensity, and off-flavor intensity on 100-point continuous line scales. Consumer sensory panelists evaluated samples for juiciness, tenderness, flavor liking, beef-like flavor intensity, beef-fat like flavor intensity, and overall liking on a 100-point continuous line scales anchored on both ends with descriptive terms. Additionally, panelists were asked to classify each sample as acceptable or unacceptable for each of the sensory traits previously listed and to assess the quality of the sample by identifying if the sample was unsatisfactory, everyday quality, better than everyday quality, or premium quality. Furthermore, the following assays were also conducted: fat percentage, moisture percentage, cook time, cook yield, cook loss, and Warner-Bratzler Shear Force. Overall, bone state had a minimal impact on palatability traits evaluated through trained sensory evaluation. Choice steaks were rated higher (P < 0.05) than Select steaks for all palatability traits evaluated. Bone state had no impact (P > 0.05) on initial juiciness, sustained juiciness, myofibrillar tenderness, overall tenderness, or off-flavor intensity in strip loin, tenderloin, and ribeye steaks. Other than strip loins, bone-in samples had a more (P < 0.05) intense beef flavor. Similarly, consumer sensory analysis revealed Choice steaks were rated higher (P < 0.05) than Select steaks for juiciness, tenderness, flavor, and overall liking. Bone state had no impact (P > 0.05) on consumer juiciness and overall liking for tenderloins and ribeyes, but in the strip loin, bone-in steaks were rated juicier (P < 0.05) and higher for overall liking (P < 0.05) when compared to boneless steaks. Moreover, bone state had no impact (P > 0.05) on consumer tenderness and flavor ratings for any of the three cuts. Regardless of bone state, tenderloin steaks were juicier, more tender, more flavorful, and rated higher overall (P < 0.05) than ribeyes and boneless strip loin steaks. Choice steaks had a higher (P < 0.05) percentage of consumers that rated juiciness as acceptable when compared to Select steaks. Furthermore, bone state had no impact (P > 0.05) on the percent of consumer’s rating juiciness as acceptable for tenderloins and ribeyes, but in strip loins, bone-in steaks had a higher (P < 0.05) percent of acceptable consumers responses than boneless cuts. Tenderloins had a higher (P < 0.05) percentage of acceptable ratings for tenderness than strip loins and ribeyes. When evaluating WBSF, Choice steaks were more (P < 0.05) tender than Select samples. Bone state did not (P > 0.05) have an impact on shear force values within any of the cuts. However, tenderloin steaks had lower (P < 0.05) shear force values than strip loin and ribeye samples. Select steaks were higher (P < 0.05) yielding and had a greater (P < 0.05) cook loss than Choice samples. Bone state also had a significant (P < 0.05) impact on cooking time, yield, and cook loss of strip loin, tenderloin, and ribeye samples. All Choice samples from each cut / bone state had a greater (P < 0.05) fat percentage than Select samples of the same cut / bone state. Bone state only impacted fat percentage in Select tenderloin steaks. Boneless Select tenderloins were higher (P < 0.05) in fat than bone-in Select tenderloins. Furthermore, all USDA Select cut / bone state combinations were higher (P < 0.05) in moisture than all Choice cut / bone state combinations, except for Choice boneless tenderloins, which are similar (P > 0.05) to Select boneless tenderloin samples. Results indicated that the same eating experience can be derived from a boneless steak as a bone-in steak of the same quality grade.
Keywords: Bone-in; Boneless; Beef; Palatability; Tenderloin; Sensory analysis